Determinación de la eficacia in vitro de chenopodium ambrosioides “Paico” en Ascaris suum, trichuris trichiura - García Navarro, Edwin (2002)
The evaluation of the action of the solid components of Chenopodium ambrosioides on Ascaris suum and Trichuris trichiura, in Vitro. Be used 120 parasites adults for each one of the species, to concentrations of 4 mgjml, 6 mgjml, 8 mgjml distributed in groups, witness, control positive (albendazole) and problem. To assess effects, deworming of the plant used, we used concentrations that were more effective on Ascaris suum and Trichuris trichiura. It was found that the concentration of 8 mgjml ssfe. Chenopondium ambrosioides presented anthelmintic efficiency in Ascaris suum (6 hours) and Trichuris trichiura 12 hours) 1.2 ssfe mgjml; producing is immobility, spasticity, concluding that Chenopondium ambrosioides is effective against Ascaris suum and Trichuris trichiura.